The Efficacy and Safety of Roxadustat for Anemia in Patients With Chronic Kidney Disease: A Meta-Analysis - Wang, Lijun; Yin, Heng; Yang, Liling; Zhang, Fenglian; Wang, Song; Liao, Dan (Frontiers in Pharmacology, 2022)
Background Chronic kidney disease (CKD) is a global public health problem, and anemia is a common complication in CKD patients. Roxadustat(FG-4592) is a new type of oral hypoxia-inducible factor(HIF) stabilizer. Studies have shown that roxadustat can maintain and increase hemoglobin concentrations better than placebo or erythropoietin. This meta-analysis was designed to evaluate the efficacy and safety of roxadustat. Methods: We performed a thorough search for randomized controlled trials of roxadustat for the treatment of anemia in patients with CKD in CBM, CNKI, VIP, Wanfang Database, PubMed, Cochrane Library, Embase, and Web of Science. We screened the studies according to strict criteria and evaluated their quality according to the Cochrane 5.1.0 evaluation handbook for randomized controlled trials（RCTs）. Data were extracted and synthesized with RevMan 5.3 for meta-analysis. Results: A total of 9 RCTs and 1364 patients with chronic kidney disease anemia were included. The overall quality of the included studies was acceptable. The results of the meta-analysis showed that roxadustat can significantly increase hemoglobin, transferrin, and total iron binding capacity(TIBC)in both dialysis-dependent (DD) patients and non-dialysis-dependent (NDD) patients: Hemoglobin(Hb): DD: [SMD=0.23, 95% CI (0.01, 0.44), p=0.04], NDD: [SMD=2.08, 95% CI (1.23, 2.93) p<0.000001]; transferrin: DD: [SMD= 0.78, 95% CI (0.24, 1.32), p=0.004], NDD: [SMD=1.37, 95% CI (0.76, 1.98), p<0.0001]; TIBC: DD [SMD=0.97, 95% CI (0.64, 1.29), p<0.00001], NDD [SMD=1.34, 95% CI (0.9, 1.78), p<0.00001]. In the dialysis group, the patients’ serum iron level was significantly higher than that of the control group after roxadustat treatment, but there was no significant difference in the NDD group [SMD=0.42, 95% CI (0.27, 0.57), p<0.00001]. In the NDD group, hepcidin, ferritin, and transferrin saturation(TSAT)were significantly reduced after roxadustat treatment: Hepcidin [SMD=-1.59, 95% CI (-2.69, -0.49), p=0.005], ferritin [SMD =-0.51, 95% CI (-0.72, 0.3)p<0.00001], TSAT [SMD=-0.41, 95% CI (-0.62, 0.2), p<0.0001]. In terms of safety, adverse events(AE) [SMD=1.08, 95% CI (0.98, 1.18) p=0.11] and serious adverse events(SAE) [SMD=1.32, 95% CI (0.97, 1.9) p=0.08] were not significantly different between the two groups. Conclusion：Roxadustat can improve anemia in NDD patients with chronic kidney disease, and its short-term safety was not significantly different from that of the comparison group